THE EFFECT OF GREEN ACCOUNTING IMPLEMENTATION, SUSTAINABILITY REPORT, ASYMMETRIC INFORMATION, AND FINANCIAL PERFORMANCE ON FIRM VALUE - Saputra, Mashari; Windyastuti, Windyastuti (UTSAHA: Journal of Entrepreneurship, 2024)
This research examines the effect of green accounting, sustainability report, asymmetric information, and financial performance on firm value. Green accounting and sustainability reports are becoming more important as awareness of sustainability and corporate social responsibility increases. On the other hand, asymmetric information can affect investors’ decisions, while financial performance is often a primary indicator in company valuation. The basic materials sector companies are concerned with the environment. Besides the environment, companies also need to be concerned about social issues, balanced information, and financial performance. By analyzing these factors, this research aims to determine whether green accounting, sustainability report, asymmetric information, and financial performance affect firm value. Firm value is measured by Tobin’s Q ratio, while other variables are measured by methods such as PROPER for green accounting, CSRIj for sustainability report, Bid Ask Spread (BAS) for asymmetric information, and Return on Assets (ROA) for financial performance. Data was taken from the company website, IDX, and the Ministry of Environment and Forestry, with a sample of 77 basic material sector companies listed on the IDX for the 2019-2022 period. Data analysis was conducted with multiple regression using Excel and SPSS 23. The results of this research indicate that green accounting and sustainability reports affect firm value. While asymmetric information and financial performance have no effect on firm value.